Pulmonary function testing for the primary care nurse practitioner. Issue 12 (December 2021) - Smith, Whitney; Chinnis, Simone; Durham, Catherine; Fowler, Terri
Abstract : Abstract: Knowledge of which pulmonary function tests are commonly performed in primary care and interpretation of their results is integral for the diagnosis, care, and management of those with pulmonary symptoms. This article provides an overview of the most common pulmonary function tests and interpretation of their results. Abstract : Knowledge of which pulmonary function tests are commonly performed in primary care and interpretation of their results is integral for the diagnosis, care, and management of those with pulmonary symptoms. This article provides an overview of the most common pulmonary function tests and interpretation of their results.